2016
DOI: 10.1186/s12889-016-3010-4
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of the Bristol girls dance project

Abstract: BackgroundThe Bristol Girls Dance Project was a cluster randomised controlled trial that aimed to increase objectively measured moderate-to-vigorous physical activity (MVPA) levels of Year 7 (age 11–12) girls through a dance-based after-school intervention. The intervention was delivered in nine schools and consisted of up to forty after-school dance sessions. This paper reports on the main findings from the detailed process evaluation that was conducted.MethodsQuantitative and qualitative data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
1
26
0
3
Order By: Relevance
“…Previous studies have identified drift (when adaptations are not in line with the spirit or theoretical underpinning of the intervention) 94,95 in intervention delivery; however, this was not commonly seen in the delivery of PLAN-A. Consistent with previous research in which PA/educational intervention deliverers have been trained to deliver sessions based on SDT, 94,97,98 this study suggests that trainers welcome the approach, and that it is possible to train deliverers to adopt this method and for them to deliver it in practice. Refinements to the train the trainers elements are shown in Appendix 20.…”
Section: Trainer Recruitment and Train The Trainerssupporting
confidence: 69%
“…Previous studies have identified drift (when adaptations are not in line with the spirit or theoretical underpinning of the intervention) 94,95 in intervention delivery; however, this was not commonly seen in the delivery of PLAN-A. Consistent with previous research in which PA/educational intervention deliverers have been trained to deliver sessions based on SDT, 94,97,98 this study suggests that trainers welcome the approach, and that it is possible to train deliverers to adopt this method and for them to deliver it in practice. Refinements to the train the trainers elements are shown in Appendix 20.…”
Section: Trainer Recruitment and Train The Trainerssupporting
confidence: 69%
“…Process evaluations are critical to understanding implementation success and the contextual factors that influence how an intervention works. However, on the basis of the pool of studies included in this review, process evaluations are rare: only 24% (n = 4) of included trials conducted a process evaluation . Three of these process evaluations assessed the issue of intervention fidelity, each concluding wide variance in implementation of the program across schools and settings.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several extensive process evaluations which have used multiple methods for data collection, similar to the WAVES study, have been undertaken [13, 15, 22]. However, reporting tends to focus on the findings of each method (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, data collection methods limited to questionnaires [9, 10], survey data [11], or qualitative data [5, 12], provide no opportunity for data triangulation. The MRC guidance has increased recognition of the importance of using multiple methods for process evaluation data collection [1315] (usually a combination of observations, logbooks, questionnaires and qualitative methods [6]), however guidance for amalgamation and analysis of such data is lacking.…”
Section: Introductionmentioning
confidence: 99%